KEUNGGULAN BERSAING MELALUI INOVASI BISNIS SEBUAH DESAIN : KREATIVITAS ORGANISASI, KOMPETENSI KEWIRAUSAHAAN DAN ORIENTASI PASAR - Reniati Reniati (Indonesian Journal of Economics and Business, 2012)
The purpose of this study is to get considerable study the influence of organizational creativity, entrepreneurial competence, market orientation on business innovation, and its impact on competitive advantage in small and medium sized Coastal Batik industry. The method used by the survey method, which is done through descriptive and eksplanatory survey. The unit of analysis of this study is a company with a number of observation units 164 companies, consisting of employers, employees and customers, the total number of respondents is 820 people. To test the hypothesis of the study used statistical multivariate statistical  and the SEM test. As for the processing of data using the program LISREL 8:50.The study's findings: SME’s Coastal Batik can be categorized into 4 quadran there are  the orientation of the art,  orientation of superior, orientation of traditional and  orientation of pragmatic. SME’s Coastal Batik dominant is a traditional orientation and focus on the resource-based production oriented and not lead to a market based. Conclusion:The creativity organization, the competence of entrepreneurship, market orientation have positive and significant both  simultaneous and partial to business innovation and have impact to competitive advantage.